ZERO PRODUCED WATER DISCHARGE INNOVATION IN PRODUCTION FLUID MANAGEMENT FOR SUSTAINABILITY AND FINANCIAL EFFICIENCY - Gunawan, Rizky
Pertamina is leading Indonesia's energy transition with a commitment to achieving Net Zero by 2060 or sooner. Pertamina Hulu Indonesia (PHI) Tanjung Field is reevaluating its activities to align with these sustainability goals, focusing on production fluid processing. This research employs the Plan-Do-Check-Action (PDCA) approach, life cycle assessments, and focus group discussions to identify priority issues. Root causes are analyzed using fishbone diagrams, Failure Mode Effect Analysis (FMEA), Pareto diagrams, and risk map analysis. The Analytic Hierarchy Process (AHP) led to adopting the CSSR (Contain, Sediment, Separate, Recovery) innovation for production fluid processing. This innovation aims for zero produced water discharge, boosting processing efficiency from 66.63% to 97.54% by the second year. During the trial period, Biological Oxygen Demand (BOD) removal efficiency reached 85.0%, and Chemical Oxygen Demand (COD) removal was 84.4% > 80%, complying with PermenLHK No. 68, 2016. Optimizing produced water usage significantly reduces the need for clean water in the injection program by 83.1%, saving 8617.4 m³. The innovation's efficiency ratio of 11.10 indicates substantial savings and revenue generation, with expected savings of IDR 7,368,139,806 and an ROI in four months, alongside the recovery of 136 barrels of oil. The implementation of the CSSR innovation is projected to reduce production residues by 83.35% > 50%, from 635.91 tons before the innovation to 105.85 tons in the second year, complying with PP RI No. 22, 2021. Energy consumption is expected to decrease by 94.96%, from 248,044 GJ to 41,076 GJ in the second year, saving 131,431.14 kWh (473.15 GJ). Electricity usage cuts will reduce CO2 emissions by 100.07 tons CO2 eq., achieving a 95% reduction from 52.46 tons CO2 eq. to 2.64 tons CO2 eq., with a trial period reduction of 12% > 4.14%, surpassing PerPres RI No. 98, 2021 requirements. The CSSR innovation supports multiple SDGs: Clean Water and Sanitation (SDG 6) by reducing clean water usage; Affordable and Clean Energy (SDG 7) by cutting electricity use and emissions; Responsible Consumption and Production (SDG 12) by minimizing residues; Climate Action (SDG 13) by lowering emissions; and Life Below Water (SDG 14) by preventing water contamination.